The Effect of Oxygen Gas Flow Rate on TiO2 Thin Film Prepared by Double Zone CVD Technique - Mohd Haron, Nurul Amira; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2020)
The research was conducted to determine the deposited TiO2 thin film of titanium dioxide on a 210º C and 60º C glass substratum using a double zone Chemical Vapor Deposition (CVD) furnace. Through a different oxygen gas, the flow rate was varied in range of 0.6 ml 1.2 ml. The effect of oxygen gas flow rate thin films was routinely tested at room temperature on titanium dioxide TiO2 and will be annealed at a fixed time, which is 1 hour at 500º C. The crystal structure properties on TiO2 was obtained using X-Ray Diffraction (XRD). In addition, the studies of surface morphology was performed using Atomic Force Microscope (AFM) and Field Effect Scanning Electron Microscopy (FE-SEM). The TiO2 electrical properties were evaluated to obtain its resistivity and conductivity using a four-point probe. The characterization of TiO2 thin film conducted more systematically and discussed in these research studies.